1980
DOI: 10.1093/infdis/142.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella pertussis Respiratory Tract Infection in the Mouse: Pathophysiological Responses

Abstract: The influence of living Bordetella pertussis on the induction and duration of pathophysiological reactions in mice infected intranasally with graded doses of culture was studied. Lethally infected mice showed loss of body weight, spleen atrophy, pronounced hypothermia and hypoglycemia, and highly elevated levels of leukocytes and serum immunoreactive insulin. Sublethally infected mice showed normal weight gain, practically normal temperature, spleen enlargement, lesser pronounced hypoglycemia, lower but signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
2
2

Year Published

1982
1982
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 21 publications
2
51
2
2
Order By: Relevance
“…This is in contrast to the results of our studies in B. pertussis-infected mice which have shown consistently both hyperinsulinaemia and hypoglycaemia (Pittman et al, 1980;Furman et al, 1981Furman et al, , 1986). We do not know if the hyperinsulinaemia in patients with pertussis is mediated via the same mechanisms as those in mice.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to the results of our studies in B. pertussis-infected mice which have shown consistently both hyperinsulinaemia and hypoglycaemia (Pittman et al, 1980;Furman et al, 1981Furman et al, , 1986). We do not know if the hyperinsulinaemia in patients with pertussis is mediated via the same mechanisms as those in mice.…”
Section: Discussioncontrasting
confidence: 99%
“…1 B). Control rats showed only a fairly constant and low level of coughing throughout each experiment and each paroxysm usually contained fewer individual coughs (c. [3][4][5] than in the infected animals (c. 5-10 or more [20-501 during the peak period). There was more coughing when the BP-sus was administered intranasally, with a moderate peak between days 9 and 14.…”
Section: Comparison Of Diflerent Methods Of Infectionmentioning
confidence: 96%
“…In the absence of a human challenge model of B. pertussis infection, studies of respiratory tract colonization and disease caused by B. pertussis have been limited to animal models, of which the most well established and frequently used is the mouse intranasal inoculation model. In this model, although overt symptomatic disease is not elicited, several characteristics of the human infection are reproduced, such as multiplication and clearance of the bacteria, limitation of infection to the respiratory tract, increased severity of infection in young animals, and various systemic physiological changes (8,25,29,37). Recent studies have shown that this may also be a useful model for the preclinical assessment of acellular pertussis vaccine efficacy (6, 19).…”
mentioning
confidence: 99%